Gender equality and modernity in Portugal. An analysis on the obstacles to gender equality in highly qualified professions - Amâncio, L. (2021)
In this review article, we argue that the transformations related to the modernisation of Portuguese society triggered by the implementation of democracy did not fully accommodate gender equality. In particular, when we consider the areas where the most progress has been made in keeping with a broadly shared urge for modernisation, education and science; whereas women have contributed to boosting the Portuguese population’s level of education, thus inverting the worst legacy of the dictatorship and developing scientific research, gender inequalities are still visible in highly qualified professions. Reviewing the results of studies from different professions, science, medicine and engineering, our analysis illustrates several factors that hinder not only the recognition of women’s competences and merit at work but also their career opportunities. Some of these factors are rooted in the type of gender ideology that was central to the propaganda of the dictatorship, thereby establishing continuity with the previous regime that seems particularly difficult to break in the absence of women’s voices to raise awareness on gender equality.